2014
DOI: 10.1530/erc-13-0508
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor beta in prostate cancer: friend or foe?

Abstract: Prostate cancer is the commonest, non-cutaneous cancer in men. At present, there is no cure for the advanced, castration-resistant form of the disease. Estrogen has been shown to be important in prostate carcinogenesis, with evidence resulting from epidemiological, cancer cell line, human tissue and animal studies. The prostate expresses both estrogen receptor alpha (ERA) and estrogen receptor beta (ERB). Most evidence suggests that ERA mediates the harmful effects of estrogen in the prostate, whereas ERB is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
2
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 148 publications
(212 reference statements)
2
70
2
5
Order By: Relevance
“…A further study has reported that the expression of ERα and aromatase (CYP19) with the R264C polymorphism, a missense SNP located on the CYP19A1 locus, has been shown to result in shorter progression-free survival and an increased risk of developing CRPC in a study of 115 men treated with docetaxel. Taken together, these observations support the hypothesis that ERα can act as an oncogene by mediating the adverse effects of oestrogen in the prostate (Nelson et al 2014).…”
Section: Oestrogen Receptors (Erα or Nr3a1 And Erβ Or Nr3a2)supporting
confidence: 83%
“…A further study has reported that the expression of ERα and aromatase (CYP19) with the R264C polymorphism, a missense SNP located on the CYP19A1 locus, has been shown to result in shorter progression-free survival and an increased risk of developing CRPC in a study of 115 men treated with docetaxel. Taken together, these observations support the hypothesis that ERα can act as an oncogene by mediating the adverse effects of oestrogen in the prostate (Nelson et al 2014).…”
Section: Oestrogen Receptors (Erα or Nr3a1 And Erβ Or Nr3a2)supporting
confidence: 83%
“…Interestingly, higher levels of ERβ correspond to lower survival in HNPC cells through the activation of pAR(s210), although the exact mechanism remains unknown. Additionally, ERβ1 has been proposed to form a complex with AR, resulting in the transcription of AR-dependent genes in PCa (76). Moreover, its spliced variants, ERβ2 and ERβ5, have tumor-promoting actions and are stimulated after dimerization with ERβ1.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, these model cell lines are not reflecting the complex cross-talk between AR, ERα and ERβ and other stromal:epithelial interactions known to occur in vivo (76).…”
Section: Erβ Agonistsmentioning
confidence: 98%
“…Whereas androgen deprivation through antiandrogens or orchiectomy is expected to protect against prostate cancer (69), the role of exogenous estrogen and its action on estrogen receptors α and β also needs to be considered. Recent literature indicates that estrogen receptor α stimulates prostate carcinogenesis, while estrogen receptor β appears to exert an antineoplastic effect, although studies suggest that different estrogen receptor β isoforms may have different and sometimes opposing modes of action (70)(71)(72). Estrogen receptors are not the only target of estrogen; it has been shown that 17β-estradiol can bind to androgen receptors with the assistance of coactivators or androgen receptor mutations that result in 17β-estradiol hypersensitivity (73,74).…”
Section: Possible Effects Of Cross-sex Hormonesmentioning
confidence: 99%